1990
DOI: 10.1111/j.1399-0004.1990.tb03525.x
|View full text |Cite
|
Sign up to set email alerts
|

A familial interstitial deletion of the long arm of chromosome 21

Abstract: A mother and daughter with an interstitial deletion of the chromosome segment 21qll to 21q21.3 have similar minor dysmorphism and mild mental retardation. These two patients are compared to others in the literature with deletion of the same region of chromosome 21. Molecular analysis of DNA from our patients localizes the DNA segments D21S1, D21Sl1, D21S8, and D21S22 within the deleted region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Only a few individuals with partial deletions of chromosome 21q have been reported, with three distinct phenotypes. First, six individuals from two families with small centromeric deletions of 21q11.1–q21.2 had normal intelligence [Korenberg et al, 1991; Aviv et al, 1997], and another whose deletion extended to 21q21.3 had mild mental retardation [Roland et al, 1990]. Next, at least five patients with deletion 21q22.3 had holoprosencephaly [Aronson et al, 1987; Estabrooks et al, 1990; Muenke et al, 1995], and one individual with a small telomeric deletion of 21q22.3 had normal intelligence [Falik‐Borenstein et al, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few individuals with partial deletions of chromosome 21q have been reported, with three distinct phenotypes. First, six individuals from two families with small centromeric deletions of 21q11.1–q21.2 had normal intelligence [Korenberg et al, 1991; Aviv et al, 1997], and another whose deletion extended to 21q21.3 had mild mental retardation [Roland et al, 1990]. Next, at least five patients with deletion 21q22.3 had holoprosencephaly [Aronson et al, 1987; Estabrooks et al, 1990; Muenke et al, 1995], and one individual with a small telomeric deletion of 21q22.3 had normal intelligence [Falik‐Borenstein et al, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…Two patients with developmental delay due to deletions of 21q11.2–q21.1 and 21q21.1–q22.3 were previously described [Huret et al, 1995]. Additionally, two patients with mild mental retardation and short stature were shown to have deletions of 21q11.2–q21.1 and 21q11.2–q21.3, respectively [Roland et al, 1990]. Another child without mental retardation had small testes and was shown to have a deletion of 21q11.2–q21.3 [Korenberg et al, 1991].…”
Section: Discussionmentioning
confidence: 99%
“…For delineation of sub-syndromes, further cases of del(2 1 q) should be studied with molecular techniques in order to precisely define the breakpoints and the genetic imbalance, as has been done by Roland et al (1990), Korenberg et al (1991), Courtens et al (1994) and in the present study. Furthermore, more complex situations could be revealed by molecular analysis: 1) In our case 1, a microduplication within 2 1q22.3 was found in addition to the visible deletion; 2) The case published by Mikkelsen & Vestermark (1 974) was reassessed by Petersen et al (1992), who found that the monosomic cell line in blood has progressively been replaced by a disomic cell line with uniparental isodisomy.…”
Section: Discussionmentioning
confidence: 99%